Ayurvedic Management of Pemphigus Vegetans (International Journal of Ayurveda and Pharma Research, 2024)
Pemphigus vegetans is a group of autoimmune disorder characterized by mucocutaneous bullae or pustules that erode to form hypertrophic papillated plaques that predominantly involve the scalp, and the face. It is the rarest variant of pemphigus vulgaris representing about 1-2% of all pemphigus. It may be correlated with Kardama visarpa in Ayurveda. The contemporary management of pemphigus is by systemic steroids. This case report of a 38 year old, male patient diagnosed with Pemphigus vegetans who presented with pustular lesions with foul smell, reddish spots with hypertrophic papillated lesions on scalp, itching and burning sensation over various body parts especially on upper parts since 20 years. He was treated with both Samana as well as Sodhana therapies for about 1 month. This condition was assessed using Pemphigus diseases area index. After treatment there was a significant reduction in the score. Moreover no new lesions were formed suggesting non progression of the diseases.